La confiance en gestion : un regard pluridisciplinaire - Harrisson, Denis (Relations industrielles / Industrial Relations, 2012)
The article reviews the book, "La confiance en gestion : un regard pluridisciplinaire," by Anne Gratacap and Alice Le Flanchec.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Auteurs et textes classiques de la théorie des organisations - Harrisson, Denis (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, "Auteurs et textes classiques de la théorie des organisations," edited by Laurent Bélanger and Jean Mercier.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les conditions de la confiance entre gestionnaires et représentants syndicaux dans un contexte d’innovations - Laplante, Normand; Harrisson, Denis (Relations industrielles / Industrial Relations, 2008)
Cet article analyse les conditions associées au développement de la relation de confiance entre les gestionnaires et les représentants syndicaux au sein d’entreprises qui ont adopté des innovations de différentes formes. Nous nous intéressons à la confiance entre des agents qui interviennent au nom de commettants. Notre étude démontre que si le développement de la confiance bénéficie d’un climat de travail moins conflictuel, d’autres conditions sont également requises, particulièrement le partage des informations entre les parties. Par ailleurs, un contexte de transformation peut améliorer la relation de confiance, particulièrement lorsqu’un processus participatif confiant un rôle au syndicat est adopté pour introduire les innovations. Celles-ci peuvent ainsi favoriser le développement de la confiance cognitive entre les parties, tout en respectant des intérêts spécifiques à chacune., This article examines the development of relationships of trust between managers and union representatives in a context of social innovations. Trust acts as a social lubricant and thus plays an important role in social relations within organizations undergoing change and which depend more on cooperation. However, trust is a multidimensional concept that appears in various forms that can be dichotomized between cognitive trust, which is based more on knowledge and reason, and identity-based trust, which is more emotional and may even involve holding common values. Within organizations, studies of trust have most often examined relations between workers and managers, or even members’ trust in their organization. Few studies have examined the relationship of trust between employers and unions. However, the interactions between institutional agents at work tend to encourage the development of the cognitive dimension of trust rather than its identity-based dimension. While encouraging cooperation between these agents and leading them to develop new relationships outside the traditional institutional framework, innovation nevertheless conceals two essential conditions for the development of trust: the interdependence of actors, and risk in the face of the future and unknown behaviour of their counterpart. Trust is not a given, but is rather a social construction that develops through the interactions of the actors at work according to the diverse conditions that we will examine. The data come from a study on new work relations between employers and unions. The sample includes union representatives and managers in goods and services firms that adopted different kinds of innovations. One thousand firms, each with more than 50 workers, were included in the study. A total of 242 union representatives and 221 managers returned their questionnaires. The sample was generally characterized by medium- or large-sized firms with a high proportion of male workers occupying permanent positions and with several years of seniority. However, there are differences between manufacturing sector firms and services sector firms. The latter employ more women who are less likely to have permanent positions and who have fewer years of seniority. Trust was measured using the average of four dimensions of the Butler scale: integrity, discretion, promise of results, and overall trust. The alpha coefficient of this trust indicator is 0.93 for both union representatives and managers. A second dependent variable measures the improvement in the trust relationship following the adoption of the innovation that the respondent considers to be the most significant. The two dependent variables (trust relationship and improvement of this relationship) have been analyzed using multiple regression and according to a model that includes several dimensions: socio-demographic characteristics, socio-economic context, labour relations climate, access to information, types of innovations, implementation process for innovations and their impacts. The union representatives indicated a lower level of trust (3.15 vs. 3.81/5) and fewer of them believe that trust increased following the adoption of the most significant innovation (27% vs. 44%). The differences between the union representatives and managers remain significant, after adjustment for different dimensions of the analytical model. This shows that the relationship is asymmetrical: the union representatives have less control over the situation and feel more vulnerable to potential opportunistic behaviours on the part of their management counterpart. Nevertheless, both the trust relationship and its improvement following the adoption of the most significant innovation are influenced by different dimensions of the analytical model. First of all, both the managers and the union representatives in the manufacturing sector are less likely than those in the services sector to feel trust. Trust is not highly related to the socio-economic context, although managers have more trust when the work force is declining; the trust of union representatives is lower when subcontracting increases. Trust is influenced by the labour relations climate. Thus trust is lower when there are more grievances or when grievances are increasing. However, trust is stronger when grievances tend to be resolved internally. Trust is also higher when respondents have access to the information requested from their counterpart. Innovations also influence trust, which is lower following the adoption of monetary innovations, but higher when other types of innovations are adopted: labour relations, work organization, training. The process of adopting innovations is important for improving the trust relationship, both when they are adopted to respond to human factors rather than factors linked to productivity, as well as when they are established through a negotiation process and a joint monitoring mechanism. Finally, negative impacts decrease trust while positive impacts do not influence the relationship of trust between union representatives and managers. The study revealed the factors that can favour the development of a relationship of trust between union representatives and managers following the adoption of social innovations. The process of adopting these innovations rather than the type of innovations seems to have a more important impact on the improvement of the trust relationship. However, this development should not be seen as an automatic transposition of the trust relationship to other members of the organization. Another question to be addressed is to what extent trust can be built without the parties losing their own identity. Our results support those of other studies that seem to show that although the cognitive dimension of trust can be developed readily between the agents at work, this is not true of identity-based trust., Este artículo analiza las condiciones asociadas al desarrollo de la relación de confianza entre directivos y representantes sindicales al interior de empresas que han adoptado diferentes formas de innovaciones. Nos interesamos a la confianza entre agentes que intervienen en nombre de comitentes. Nuestro estudio demuestra que si el desarrollo de la confianza beneficia de un clima de trabajo menos conflictivo, otras condiciones son igualmente requeridas, particularmente el hecho de compartir las informaciones entre las partes. De otro lado, un contexto de transformación puede mejorar la relación de confianza, particularmente cuando se adopta un proceso participativo para introducir las innovaciones, confiando así un rol al sindicato. De esta manera, estas innovaciones pueden favorecer el desarrollo de la confianza cognitiva entre las partes sin dejar de respetar los intereses específicos de cada uno.

Rebâtir la confiance après une grève de longue durée : est-ce possible ? - Bonin, Geneviève A.; Harrisson, Denis (Relations industrielles / Industrial Relations, 2008)
Cette étude a pour but d’analyser les facteurs contribuant à bâtir la confiance entre employés syndiqués et cadres après une grève de longue durée dans une succursale bancaire. Des entrevues semi-dirigées auprès de treize employés et cinq cadres, des observations et une analyse documentaire ont servi à déterminer ces facteurs. Ces derniers ont été analysés à la lumière des écrits scientifiques pour établir un modèle relationnel et analyser la situation vécue par les membres de l’organisation à l’étude., The effects of strikes have always preoccupied industrial relations’ scholars and practitioners. Even though statistically, there have been fewer strikes in Quebec during the last few years, they have not been of lesser interest. The most recent strikes have been more apparent because of their longer duration. This study discusses trust between managers and unionized employees who have returned to work after a fourteen-month strike. The objective is to better understand the phenomenon of trust in a situation of organizational conflict and, more precisely, to analyze the factors that contribute to re-establishing trust between union employees and managers following this major conflict. A few theoretical concepts about trust help us understand the basic elements needed to produce collaborative relationships. Among other things, categories of trust established by Lewicki and Bunker (1996) as well as Zucker (1986) are presented to help make a better judgment with regard to the different types of relationships and to understand the way in which they present themselves in particular situations. This section ends with an overview of the authors’ theoretical perspective, an institutional approach, which makes reference to Powell and Dimaggio’s (1991) framework. Because of the difficulty to access multiple companies affected by a strike, a qualitative case study was conducted. Thirteen union employees and five managers chosen randomly among each job category from a total of forty-six employees make up the sample. They were interviewed during semi-structured interviews six months following the end of the strike. Observations about individual behaviour during the interview period were also taken into consideration. An analysis of internal documents from the organization helped bring out factual information about the state of the relationship between the two groups before, during and after the strike. It is the use of these three traditional methods that helped construct the case presented. Not only does it explain the events surrounding the conflict by using a balanced approach including information obtained from union employees and company managers, but it also includes references to articles published in local newspapers to give a temporality and a sense of place to the events. Subsequently, the authors undertake a discussion about ways to reconstruct trust among the parties. Tables detailing the factors that can contribute to reconstructing trust according to each party are presented with representative quotes from the semi-structured interviews. In total, three common factors were raised—communication, material investments and human investments. Communication is a central concept, but it also includes its share of complexities because the simple act of communicating is not sufficient. Even if, in basic terms, material investments are perceived as advantages, they are not in practice, according to the literature on this subject. Human investments can also bring new dynamics to a company, but cannot be done to the detrimental need of removing existing personnel. To these factors, the union employees add six additional ones including desire, supervision, recognition and appreciation, respect of the collective agreement and the importance of not resorting to outsourcing. The managers also came up with four additional factors—responsibility, comprehension, company vision and the importance of providing projects to union employees. All these factors are systematically analyzed in the article in direct relation to the written scientific and theoretical literature on these subjects. In light of this analysis, it is possible to establish a relationship between these factors and a hierarchy of their importance that can serve to explore the possibility of reestablishing trust within the organization. These relationships and this hierarchy are presented in an illustration which summarizes the study. Explanations about its creation and the way to interpret it are also included. It is important, however, to note that although the study reveals a number of important factors needed to study trust, it has its limitations which can only be rectified by studying each factor in a distinct fashion and by weighing each one individually during subsequent research. In conclusion, this research demonstrates the difficulty to establish trust within an organization because the company does not recognize the union’s presence and its role. The company is rather searching to achieve its own objectives without taking the values and interests of its employees into account as well as those of the trade union. From a theoretical point of view, the study helps identify the limitations to trust relationships between various groups of employees, the effects of strikes on returning to work and of trust in the after-strike context. Paths for future research are explored. It is suggested to replicate the study in an institution in the same field or in different fields to open the door to the possibility of generalization. Secondly, it is suggested to weigh the factors to find out which ones would have the greatest impact on the creation of trust. And, finally, measuring the level of trust that really exists between the parties would be beneficial in understanding the scope of the division which separates them., El objetivo de este estudio es de analizar los factores que contribuyen a construir la confianza entre empleados sindicalizados y directivos después de una huelga de larga duración en una sucursal bancaria. Para determinar estos factores, se utilizaron entrevistas semi-dirigidas con trece empleados y cinco cuadros, observaciones directas y un análisis documentario. Dichos factores fueron analizados a la luz de escritos científicos para establecer un modelo racional y analizar la situación vivida por los miembros de la organización al estudio.